Effects of Ocular Direct Current Stimulation on Full Field Electroretinogram - Blum, Maren-Christina; Solf, Benjamin; Hunold, Alexander; Klee, Sascha (Frontiers in Neuroscience, 2021)
Studies on weak current stimulation (1–2 mA) examine effects on neuronal cells for the treatment of neurological diseases, like depression. Ocular current stimulation showed positive effects on retinal nerve cells which indicate that neurodegenerative ocular diseases, e.g. glaucoma, can be treated with current stimulation of the eye. However, up to now it remains unclear which exact retinal cells can be influenced. During an ocular direct current stimulation, a significant reduction of the characteristic P50 amplitude of a pattern-reversal electroretinogram (PERG) was found for an anodal and a cathodal stimulation. This current stimulation effect could originate from the modulation of pre-ganglion cell activity or by changes in local ON and OFF responses of ganglion cells. For clarification, we investigate acute direct current stimulation effects on a full field electroretinogram (ERG), which represents the activity of pre-ganglion cells (specifically cones and bipolar cells). The ERG from 15 volunteers was evaluated before (ERG 1) and during (ERG 2) an ocular direct current stimulation with 800 µA over 5 min. The current was applied through a ring rubber electrode placed around the eye and a 25 cm² rubber electrode placed at the ipsilateral temple. For ERG measurements, sintered Ag/AgCl skin-electrodes were positioned on the lower eyelid (active), the earlobe (reference), and the forehead (ground). The volunteers were stimulated in three independent sessions, each with a different current application (randomized order): cathodal polarity, anodal polarity (referred to the electrode on the eye) or sham-stimulation. The changes between the two ERG measurements of the characteristic full field ERG amplitudes, a-wave, b-wave, and b’-wave (b-wave measured from zero line) were tested with the Wilcoxon rang-sum test (α = 0.05). Comparing before to during the current stimulation for all applications, the ERG waves showed no effects on amplitudes or latencies. Furthermore, no significant difference between the cathodal, anodal, and sham stimulation could be found by a Friedman test. These results indicate an unlikely contribution of pre-ganglion cells to the previously reported stimulation effect on PERG signals.